Development of Santri Character Values through the Qodiriyah Naqsyabandiyah Order - Heri Saparudin; Agus Salim Mansyur; Adang Hambal; Yuyun Nurul'aen (Journal of Social Science, 2021)
The formation of good character or morality is the core of national education goals as mandated by USPN No. 20 of 2003. To be implemented in life, the process of character building needs to be carried out in a systematic, systemic and continuous way, touching the physical and spiritual dimensions, which need to be built from before birth until the end of life. Pondok Pesantren as the oldest educational institution that is attached to the journey of the nation's life still exists and has been proven to contribute to the formation of the nation's character. Suryalaya Islamic Boarding School with its Sufism and Tarekat is more focused on spiritual education in shaping the character of its practitioners. This study aims to describe family education, riyadhah, and character, as well as how the relationship between these three variables in the formation of the character of TQN pontren Suryalaya practitioners. There are two steps in optimizing the character building of TQN Pontren Suryalaya practitioners. namely: First, family education is the first and foremost find that must be built by parents in their families, especially through example and habituation. Second, riyadhah in the qodiriyah naqsyabandiyah congregation is a ritual that must be carried out continuously and seriously starting from talqin dhikr, practicing dhikr, khataman, kiamullail, manakiban, and pilgrimage. To answer the research questions, a mixed-method (quantitative and qualitative approaches) was used, with survey methods and content analysis. This study concludes several things, namely: (1) The family education of TQN practitioners is generally good, although in this modern era there is a shift in the value of family education, especially role modeling and habituation. (2) Riyadhah is a ritual practice of TQN commanders that is carried out well and consistently, although some rituals such as manaqiban and pilgrimage are still carried out by certain circles due to time constraints, while the character of TQN practitioners is classified as good. (3) Family education is positively and significantly related to the character-building of TQN practitioners at Suryalaya Islamic Boarding School. (4) Riyadhoh is positively and significantly related to the formation of the character of TQN practitioners at the Suryalaya Islamic Boarding School. (5) Family education and Riyadh are positively and significantly related to the character building of the TQN practitioners of the Suryalaya Islamic Boarding School.